Effect of fly ash on mechanical properties and morphology of plasterboard based on recycled poly(ethylene terephthalate) - H Phung, Thien An; Hoang, Dong Quy; Du, Bui Duy (Vietnam Journal of Chemistry, 2017)
The purpose of this study was to synthesize plasterboard based on recycled poly(ethylene terephthalate) (PET) and fly ash. The molecular weight determination of unsaturated polyester (UP) from recycled PET was performed by functional titration method. The effect of initiator, benzoyl peroxide (BPO) on the curing kinetic of UP from recycled PET was studied by differential scanning calorimetry (DSC) and at 2 phr BPO led to good curing process. The content of fly ash (50, 100, 150, 200 phr) at 2007 nm in diameter was used and the effect of fly ash content on some properties such as flexural strength, vickers hardness, and impact strength of plasterboard was researched. Test results showed an increase in mechanical properties, especially at 150 and 175 phr filler amount. In addition, the morphology of plasterboard at different fly ash contents was characterized by scanning electron microscopy (SEM). Also, chemical resistance of plasterboard was evaluated from the weight change in different chemical environment. Keywords. Unsaturated polyester, Recycled PET, Fly ash, Plasterboard.